THE ENZYMATIC TERMINATION OF POLYDEOXYNUCLEOTIDES BY 2′,3′-DIDEOXYADENOSINE TRIPHOSPHATE - Toji, Lorraine (1969)
The nucleoside 2′,3′-dideoxyadenosine is lethal to E. coli and blocks DNA synthesis irreversibly. The hypothesis that a derived dideoxynucleoside triphosphate is incorporated terminally into the cellular DNA has been tested in an in vitro system. The triphosphate of dideoxyadenosine was synthesized and shown to inhibit the in vitro synthesis of DNA by purified E. coli DNA polymerase. The kinetics of inhibition of nucleotide incorporation and pyrophosphate exchange were studied. Early in synthesis the dideoxynucleotide is a competitive inhibitor of the enzyme. Subsequently, synthesis is almost completely arrested. Radioactive dideoxyadenosine triphosphate was prepared. The compound was shown to be incorporated enzymatically into dAT copolymer to the extent of about one molecule per molecule of template. It is released from such templates by DNA polymerase at less than 1 per cent of the rate of release of other natural nucleotides. The label is released by snake venom phosphodiesterase far more rapidly than total nucleotides. This nucleoside triphosphate has thus been shown to be a competitive inhibitor of DNA polymerase and a terminator of polydeoxynucleotide chains.